UJI EFEKTIVITAS PENYEMBUHAN LUKA BAKAR SALEP EKSTRAK DAUN ADAM HAWA (Rhoeo discolor) PADA KELINCI JANTAN - Dila Maimunah; Na’imatul Retno F; Octaviana Dyah Oentari (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Burn wounds are tissue damage caused by exposure to heat, chemicals, or electricity. Improper treatment of burn wounds can lead to complications such as infection, wound expansion, scarring, and even death. This study aimed to evaluate the effectiveness of Adam Hawa leaf extract ointment (Rhoeo discolor) in healing second-degree burns in male rabbits. The study employed an experimental method with treatment group design, consisting of a negative control group (vaseline), a positive control group (gentamicin ointment), and three treatment groups with extract concentrations of 10%, 15%, and 20%. Burns were induced thermally, and healing was observed over 14 days by measuring wound diameter every two days. The results showed that the 20% Adam Hawa leaf extract ointment was the most effective, with an average wound diameter of 0.83 cm, compared to 15% (1.04 cm), 10% (1.13 cm), the negative control (1.73 cm), and the positive control (0.80 cm). Statistical analysis showed significant differences between the groups, with a p-value of 0.000 < 0.05. Therefore, Adam Hawa leaf extract ointment is effective in accelerating burn wound healing, particularly at a concentration of 20%.